PERENCANAAN DINAS PERHUBUNGAN KOTA PEKANBARU DALAM PEMBANGUNAN HALTE TRANSMETRO PEKANBARU TAHUN 2021 - Cindy Afanse; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Transportation is one of the keys to the development of an area or city. The development and progress in the implementation of transportation needs to be supported by good and quality planning and development and also needs to involve various groups. As in the case that occurred in Pekanbaru City related to the planning for the construction of the Trans Metro Pekanbaru City Bus Stop. Although the operation of the Trans Metro Bus has been running, in the process there are still many people in Pekanbaru who have not used the services of the Pekanbaru Trans Metro Bus as a means of land transportation that can help facilitate traffic activities in Pekanbaru City. The formulation of the problem in this study is how the Pekanbaru City Transportation Service Planning in the Construction of the Pekanbaru Trans Metro Stop in 2020. This study aims to describe the shelter development planning by the Pekanbaru City Transportation Service. In addition, this study uses a qualitative approach and data collection techniques through interviews (interviews) and documentation. The result of this study is that the planning for the construction of shelters in Pekanbaru City carried out by the Pekanbaru City Transportation Service is carried out through a government system for the convenience of the community, in this case the Government has an important role for the construction of a good shelter. The development carried out in general has touched public roads that are easily accessible by the community so that it is easier to access them. It was also found that there were obstacles in the planning for the construction of the bus stop, such as the lack of funds owned by the Pekanbaru City Transportation Service, then the process of determining the location that had problems with the community and poor coordination between stakeholders. Keywords: Planning, Department of Transportation, and Trans Metro Bus Stop